Political economy of televangelism: - Keyan G Tomaselli (Communicare)
Mass media practices are generally of a "top down' nature. Messages manufactured by media institutions favour dominant perspectives. They are transmitted unilinearly and largely exclude the voices of ordinary people, the poor and the socially marginalised. Even in transitionary moments as occurred in Zimbabwe, the pre-revolutionary flow of communication from above is rarely transformed by new 'democratic' elites. This paper contests assumptions which have led to the monopoly of media practices by dominant elites. It is argued that there are no necessary technological or theological reasons why religious broadcasting should not be of a bottom-up kind which expresses and on gages various kinds of discourses. Individuals should have freedom to explore different perspectives in terms of their own class, ethnic, historical, language, gender, and cultural experiences. In the light of this perspective, in the first section below, we offer a political economy of televangelism Televangelism we define as exhortatory messages broadcast by nondemoninational preachers who finance their network and cable programmes by appeals to their viewers (Biernatzki 1991:1). Teleministries refers to the institutional business operations and structures run by televangelists.